Digital Policing of the Dittipidsiber Bareskrim Polri in Handling Online Gambling (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study aims to analyze the digital policing of the Dittipidsiber in handling online gambling. The focus of this study includes the development of rampant online gambling in Indonesia, the organizational resources of the Dittipidsiber in handling online gambling at this time, and the policing of the Dittipidsiber in handling online gambling. The paradigm of this study is the constructivism paradigm. The research approach used by the author is a qualitative research approach. The method used by the researcher is a descriptive analysis method. The results of the study show that 1) Online gambling is a form of legal violation that needs to be eradicated. Driving factors can come from the individual himself or from the environment; 2) The condition of the resources of the Dittipidsiber Unit is still limited, especially in terms of human resources, facilities and infrastructure and budget. Meanwhile, the ICT condition of the Directorate of Cyber ​​Crimes of the National Police Criminal Investigation Unit in handling online gambling is "quite adequate" for now, although ongoing development and maintenance are still needed; 3) The policing of the Dittipidsiber in handling online gambling has basically been implemented through preemptive, preventive, and repressive strategies. Dittipidsiber in handling online gambling has also implemented communication, coordination and collaboration, both internally and externally, although the Dittipidsiber still tends to prioritize repressive strategies. The conclusion of the study show that digital policing of the Dittipidsiber in handling online gambling still need to be improved.